The influence of Snapchat ads on students buying behaviors in Saudi Arabia - Alqahtani, Hessah; Xue, Fei (Eximia, 2022)
This research is about the influence of Snapchat ads on the students’ buying behavior in Saudi Arabia. With the rampant use of social media like Snapchat, there is need to explore how the social media platforms affect people’s buying behavior. This study was conducted based on the Uses and Gratification theory (UGT). Ninety-three students from 3 different colleges in Saudi Arabia participated in the study, and answered questions related to their perception and attitude and as well as the impact of Snapchat ads on their buying decisions. The study found a strong link between Snapchat ads, attitudes and buying intentions. In addition, the students were found to be motivated by the presence of Snapchat ads in their buying decisions.